Thrombopoietin Receptor Agonist Use for Immune Thrombocytopaenia - Neunert, Cindy E. (Hämostaseologie, 2019)
Management of patients with corticosteroid-refractory immune thrombocytopaenia (ITP) possesses a significant challenge to practitioners. Until recently, options included splenectomy and immunosuppression. With improved knowledge of both thrombopoiesis and the pathophysiology of ITP, novel drug development with thrombopoietin-receptor agonists (TPO-RAs) was undertaken. Two agents, romiplostim and eltrombopag, are currently approved for use in patients with chronic ITP. Both agents have been shown to increase the platelet count, improve health-related quality of life and reduce bleeding symptoms and concomitant medication use. This review will highlight the discovery of TPO-RA agents, appraise key clinical trials and explore future directions.
Keywords: immune thrombocytopenia; thrombopoietin-receptor agonists; second-line therapy